Taxonomic Revision of Cuphea sect. Trispermum s.l. (Lythraceae) - Facco, Marlon Garlet; Cavalcanti, Taciana Barbosa (Phytotaxa, 2023)
Cuphea sect. Trispermum, one of the 13 sections of the genus, underwent a new circumscription after morphological, ecological, and molecular studies. A total of 20 species and two varieties are recognized in the section, including three new described species (C. araguaiaensis, C. auriflora, and C. praetermissa) and six species transferred from other sections. Eleven taxa were synonymized and 28 lectotypes were designated. The nectary at the base of the ovary deflexed, convex in the dorsal region, concave ventrally, three ovules, obtuse margin seeds, and pollen with the exine thickened between the pores are synapomorphies of C. sect. Trispermum, proving to be monophyletic after a broader definition. Representatives are found in Mexico, Central America, the Caribbean, northern South America, Bolivia, Paraguay, and Brazil, where 17 species occur, of which 13 are endemic. They are subshrubs to shrubs that often grow in cerrado sensu stricto, “campos rupestres” and Amazonian savannas. A high degree of narrow endemism is evident, with species restricted to specialized habitats. New information on floral and vegetative morphology, pollen, cytology, and habitat is provided for the section. In addition, keys are accompanied by descriptions, illustrations, distribution maps, and preliminary assessment of the conservation status for all taxa.